Study of Chinese household cooking practices: energy and cooking fumes - Wang, Hong (2017)
First, this research has attempted to identify the underlying reasons for high Chinese family cooking energy consumption. Second, this research has tried to identify ways of reducing Chinese kitchen cooking fume pollution. The literature review indicated that, although cooking energy takes one of the largest proportions of residential building energy consumption, previous studies in this area have not been enough. The published knowledge found indicates that urban residential buildings takes 1/4 of the national building energy consumption (excluding heating). This portion has grown continuously since 2001 in terms of energy consumption intensity (kgce/m2). Among household energy (excluding heating), cooking, home appliances and lighting are the three largest energy end users. Although the increase in cooking energy is low, partially attributed to wide adaptation to gas cooking fuel instead of coal fuel in China, it still takes the largest household energy consumption: 31% in 2011. Many research papers report different results based on field measurements of household energy end users, some of which show conflicting results. However, the literature review has confirmed that in China cooking energy consumes the second-largest amount of household energy after space heating. The literature review also pointed out that, although compared with Western counterparts, Chinese residential buildings consume less national energy, cooking takes a large percentage of household energy. A further literature review showed little valuable information underpinning the reasons for high cooking energy use in Chinese households. Some overseas research papers give hints regarding cooking energy and cooking techniques, cookware, and occupant behaviour. However, the difference in food culture traditions has led to a greater difference between Western and Chinese cooking techniques. Compared with Western countries, Chinese hot dishes require a greater number of cooking techniques. In order to find out more details of cooking energy and fume generation in real Chinese home kitchen conditions, the author used a series of research methodologies to measure and test home energy and cooking fume concentration. The results reconfirm that cooking energy is the second-largest home energy end user after space heating, along with other findings. These other findings include: • The four largest energy end users in northern Chinese households are space heating, cooking, hot water and entertainment. • Hot water, lighting and entertainment energy consumption have clear seasonal characteristics i.e., daily consumption is low in summer and high in winter. This is because of the colder weather in winter (demanding more energy to heat water) and longer nights in winter (with a longer indoor entertainment time and a greater requirement for lighting in the evening). • Daily cooking energy consumption in a given family is almost fixed, although the difference between different families is large. This could lead to further study on the underlying reasons for the difference between families. The most important finding in the research is the discovery of the relationship between home cooking energy and family life cycle. A strong relation was observed between these two factors. This was confirmed by the measurement of the test families as well as the survey of 70 random selected families. The relation is, therefore, denoted as the CookEUI (cooking energy use intensity) of the different family life cycles. Following the data analysis and survey, it was also found that the cooking energy for a certain family life cycle was constant, i.e., locked in an FLC stage until the stage changed. Finally, a database was built into the IES energy simulation using figures found in the research. This represents significant progress in home energy study. Before discovering cooking EUI, cooking energy in most pieces of energy simulation software was treated as a process load with a constant figure.